Consumer Behavior and Purchase Intention of Organic Meat: An Overview - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
The increase of interest in organic meat throughout the world is in response to concerns about the intensive agricultural practices and their effects on consumers’ health and the environment. Several researches have demonstrated that consumers have become increasingly concerned by the health risks posed by food consumption and this is reflected in the growth of organic food market in recent years across all regions, including Malaysia. However, the organic meat sector in Malaysia is still at its “infancy stage”, whereby more supports are needed to create consumer awareness in order to enhance the acceptance and stimulate the organic meat purchase in the country. The purpose of the study was to analyze the Malaysian’s consumer behavior on their purchase intention towards organic meat from various economic and marketing aspects. The overall results of this study reveal the organic meat choice motives of consumers as well as the purchasing pattern of organic meat among consumers in Klang Valley, Malaysia. This study was carried out via a structured survey throughout Klang Valley areas involving 300 respondents. Future research should focus on a similar study with the extended scope to all states in Malaysia so that the findings could be compared and generalized to the entire population in Malaysia.